Stress and mental health in adolescents and young adults with cystic fibrosis 1 year after the COVID pandemic: Findings from an Italian sample. Issue 11 (12th August 2022) - Graziano, Sonia; Boldrini, Francesca; Quittner, Alexandra L.; Fiocchi, Alessandro G.; Tabarini, Paola
Abstract: Background: The spread of COVID‐19 was associated with increased stress and new mental health concerns for people with cystic fibrosis (pwCF), already at increased risk for depression and anxiety. This study assessed stress and mental health in adolescents and young adults with CF 1 year from when the pandemic began. Methods: Sixty‐six pwCF (mean age = 24; range 14–36) completed a new measure of the impact of COVID‐19 (COVID‐19 Exposure and Family Impact Scale‐Adolescence and Young Adult; CEFIS‐AYA); the Patient Health Questionnaire‐9, and the Generalized Anxiety Disorder‐7. The Italian translation of the CEFIS‐AYA was performed. Results: On the CEFIS‐AYA, the mean Exposure score was 5.2 ( SD  = 2.6) out of 28. The mean Impact score was 1.8 ( SD  = 0.7; negative valence > 2.5). Individuals were more sedentary and undertaking less exercise. Average stress rating was 5.9 ( SD  = 2), indicating moderate stress. No significant differences were found between those who did ( N  = 12) and who did not have a COVID infection ( N  = 54). A high percentage of participants scored above the clinical cut‐off for depression (45%) and anxiety (41%), with a low proportion reporting moderate‐severe symptomatology. Conclusion: After 1 year, the pandemic was having a less significant impact on patients' daily lives. Sedentary activity and reduced exercise were common. Despite expectations that this group was particularly vulnerable, depression and anxiety scores were similar to the rates described for this population before the pandemic. Overall, these results suggested that pwCF are highly resilient and nearly 1 year after the onset of COVID‐19, have returned to similar daily activities and emotional health.